Effects of Effective Microorganism on Properties of Blended Cement Concrete - Nurul As’shikin Binti Ramli; Abd Rahman bin Mohd Sam (Human Sustainability Procedia, 2018)
Concrete is an artificial rock that is made with a mixture of cement, aggregates and water with certain proportion. Concrete is one of the material that is most widely used in the construction industry. Cracks that occurs in concrete structure require regular maintenance and special type of treatment which will be very expensive, particularly to the massive concrete structures that bear loads or main structures members. So, to overcome this problem, EM (Effective Microorganism) concrete is introduced to study the potential of EM concrete in filling the cracks. By mixing EM with concrete mixture, the effect on the properties of concrete is assessed whether this EM concrete increase the workability, strength, durability and other properties related. In this study, understanding the function and mechanism of EM in concrete is crucial. This research is undergoing a positive development nowadays in achieving sustainability of concrete, needed for environmental reasons. Several parameters and concrete properties was tested in the experimental procedure and the effect of EM in concrete were assessed in this study. The optimum mixture for EM sample that contributes to the maximum strength properties was 10% mixture of EM in the concrete admixtures. The performance of EM were measured through its fresh and hardened properties of the concrete. From this experimental study, the optimum EM mix to be added in the concrete is 10%, slump of EM concrete had increase by 11.4%. Compressive strength of the EM concrete also increase and modified compression strength is higher than cube compressive strength by the average of 5% for all samples. UPV value shows increasing pattern after concrete were pre-load at 28 days of curing, indicated that the potential of EM filling the cracks. Furthermore, the EM concrete had higher shrinkage and expansion strain compared to the control concrete. While water absorption shows that concrete with dry during condition does absorb more water because of the capillary action that occurs in dry concrete compared to concrete in water curing condition. Lastly, EM concrete show lower rate of carbonation process than control concrete by 50% because the mechanism of EM concrete had made the concrete less permeable compared to the control concrete. From this study, it can be concluded that the properties and behavior of EM concrete almost similar with the normal concrete. However, EM concrete does have the potential in filling the crack of concrete and further studied is crucial in understanding the mechanism and reaction of EM in concrete